Migration and the commoditisation of ritual : Sacrifice, spectacle and contestations in Kerala, India - Filippo Osella and Caroline Osella (Contributions to Indian Sociology 2003; 37; 109, 2003)
This article discusses relationships between ritual change and out-migration in rural Kerala, south India, via ethnography o kuthiyfottam, a sacrifice of human blood standing metonymically for full human sacrifice. Migration-in particular to the Gulf-has accelerated ongoing processes of commoditisation of ritual practices. While this has led to an overall democratisation of rituals, it has also heightened anxieties about the authenticity of ritual performances, leading to widespread and tense debates about what is traditional' and what is not. While low caste or new-moneyed sponsors do not have either the symbolic or practical capital necessary to conduct 'traditional' rituals, their ritual naiveté allows for an acceleration of processes of introduction of new styles and innovations. Migrants are thus veritable innovators, introducing new aesthetic forms and a novel sense of religiosity. But oppositions between traditional' and 'new/modern', orthodoxy and heterodoxy, authentic and inauthentic, are clearly unsettled by the ritual performers themselves: here the emphasis is on creativity, aesthetic sense and the abilities to shift popular taste and introduce new artistic performances.